2017
DOI: 10.1590/2177-9465-ean-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

User embracement and risk classification at obstetric emergency: evaluating operationalization in a maternity hospital school

Abstract: Acolhimento do usuário e classificação de risco em emergência obstétrica: avaliação da operacionalização em maternidade-escola Acogimiento del usuario y clasificación de riesgo en emergencia obstétrica: evaluación de la operacionalización en una maternidad escuela

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
2
1
5
Order By: Relevance
“…A study on the evaluation of emergency obstetric care in a reference teaching hospital in Recife analyzed 377 occurrences and found that 3.2% of women sought the service in the puerperium and, of these, 74.5% sought the service by spontaneous demand. (22) The findings of this study also contrast with the results, since 16% of the puerperal women sought the EC and 4.6% sought the service by spontaneous demand (without referral). This difference can be explained by the fact that all puerperal women who give birth in the institution are instructed to seek the unit in case of urgency/emergency.…”
Section: Discussioncontrasting
confidence: 91%
“…A study on the evaluation of emergency obstetric care in a reference teaching hospital in Recife analyzed 377 occurrences and found that 3.2% of women sought the service in the puerperium and, of these, 74.5% sought the service by spontaneous demand. (22) The findings of this study also contrast with the results, since 16% of the puerperal women sought the EC and 4.6% sought the service by spontaneous demand (without referral). This difference can be explained by the fact that all puerperal women who give birth in the institution are instructed to seek the unit in case of urgency/emergency.…”
Section: Discussioncontrasting
confidence: 91%
“…Na emergência obstétrica, 66,67% das gestantes apresentaram sintomas de depressão, enquanto, no CEMI, o percentual foi menor, sendo de 33,33%. Dessa forma, é possível fazer o questionamento sobre se o atendimento integral a essas usuárias é feito de forma a garantir o atendimento psicológico adequado em emergências obstétricas, uma vez que estudos apontaram esse setor como necessitando de reavaliações constantes e monitoramento mensal, tendo discussão entre a gestão e os trabalhadores sobre as estratégias de enfrentamento para classificar o risco e melhorar o atendimento a gestantes (Figueiroa et al, 2017).…”
Section: Discussionunclassified
“…O acolhimento constitui-se em ações técnico-assistenciais para a reorganização dos serviços e mudanças nas relações entre profissionais de saúde e usuários, por meio de parâmetros éticos, solidários e humanitários, que garantam o acesso universal com resolutividade no atendimento. Em obstetrícia, o acolhimento apresenta peculiaridades inerentes às necessidades e às demandas relativas ao processo gravídico, como a investigação de queixas comuns no período gestacional (OLIVEIRA, GUIMARÃES, 2013;FIGUEIROA, 2017).…”
Section: Discussõesunclassified